Victim Age and the Generalist Versus Specialist Distinction in Adolescent Sexual Offending. (March 2016) - Leroux, Elisabeth J.; Pullman, Lesleigh E.; Motayne, Gregory; Seto, Michael C.
More knowledge is needed about the etiology and treatment needs of adolescent sex offenders. The current study compared adolescents who had offended against children (defined as below the age of 12 and at least 5 years younger than the adolescent), adolescents who have offended against peers or adults, and adolescents who had victims in both age groups. Based on Seto and Lalumière's meta-analytic findings, participants were compared on theoretically derived factors, including childhood sexual abuse, atypical sexual interests, sexual experience, social competence, psychiatric history, and general delinquency factors (past criminal history, substance abuse history, and offense characteristics). The study sample consisted of 162 court-referred male adolescent sexual offenders aged 12 to 17 years. Of the six identified domains, groups significantly differed on five of them; the exceptions were variables reflecting social competence. The results further support the validity of distinguishing adolescent sex offenders by victim age.